The Effect of Halal Brand Personality, Brand Experience, User Experience and E-Service Quality on Brand Loyalty (Case Study on Muslim Consumers of Skintific Products in Surabaya): Pengaruh Halal Brand Personality, Brand Experience, User Experience, dan E-Service Quality Terhadap Brand Loyalty (Studi Kasus Pada Konsumen Muslim Produk Skintific di Kota Surabaya) - Sania Salsabila; Maryam Bte Badrul Munir (Universitas Islam Darul 'ulum Lamongan, 2024)
This study aims to determine the effect of halal brand personality, brand experience, user experience, and e-service quality on brand loyalty simultaneously and partially. This research uses descriptive quantitative methods. The population in this study were 100 Muslim consumers of Skintific products in Surabaya. The sample in the study was determined by the lemeshow formula and obtained 100 respondents. The sampling technique used purposive sampling. The data collection technique used a questionnaire with 36 statement items and was measured using a Likert scale of 1 to 5 which had been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis to answer the hypothesis. The results showed that from the partial test, the halal brand personality variable had a significant effect on brand loyalty with a tcount of 2.138> table 1.661 and a significant value of 0.035 <0.05. From the variable. From the brand experience variable, it has a significant effect on brand loyalty with tcount 2.055> table 1.661 and a significant value of 0.043 <0.05. From the user experience variable, it has a significant effect on brand loyalty with a tcount of 3.782> table 1.661 and a significant value of 0.000 <0.05. From the e-service quality variable, it has a significant effect on brand loyalty with tcount 2,764> table 1,661 and a significant value of 0.007 <0.05. Then, the simultaneous test of halal brand personality, brand experience, user experience and e-service quality variables has a significant effect on brand loyalty showing F count 20,261> F table 2,467 with a significant value of 0.000 <0.05. The R Square result of 43.8% shows the influence of halal brand personality, brand experience, user experience, and e-service quality on brand loyalty. While 56.2% is influenced by other variables outside the study